2021
DOI: 10.33448/rsd-v10i10.18137
|View full text |Cite
|
Sign up to set email alerts
|

Participação social no diagnóstico e prognóstico do Plano de Recursos Hídricos da Região Hidrográfica do Paraguai

Abstract: A elaboração do Plano de Recursos Hídricos caracteriza-se em um processo de estudo, diálogo e consenso contínuo, fornecendo um contexto da situação real dos Recursos Hídricos em diferentes realidades e cenários. Neste sentido o objetivo deste trabalho foi analisar o processo de participação social na elaboração do Plano de Recursos Hídricos da Região Hidrográfica do Alto rio Paraguai, entre os estados de MT e MS. Foram realizadas oficinas onde os participantes eram agrupados em categorias de stakeholders, para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(14 reference statements)
0
2
0
1
Order By: Relevance
“…The Paraguay River Basin (Figure 1) covers four riparian nation states with its water courses -Brazil, Uruguay, Paraguay, and Argentina -and shelters the complex formation of the Pantanal region, with significant international social and environmental importance, as it comprises the largest wetland in the world, as well as being listed as National Heritage of Brazil and a Biosphere Reserve designated by Unesco (Rabelo et al, 2021).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The Paraguay River Basin (Figure 1) covers four riparian nation states with its water courses -Brazil, Uruguay, Paraguay, and Argentina -and shelters the complex formation of the Pantanal region, with significant international social and environmental importance, as it comprises the largest wetland in the world, as well as being listed as National Heritage of Brazil and a Biosphere Reserve designated by Unesco (Rabelo et al, 2021).…”
Section: Study Areamentioning
confidence: 99%
“…It should be noted that the Upper and Lower Paraguay regions have -different impacts. Studies by Rabelo et al (2021) and Souza et al (2017) have identified that deforestation, followed by the inappropriate use of land for cultivation and urbanisation, accelerate erosive processes, modifying the river dynamics of the region (Upper Paraguay) and subsequently, causing an increase in sedimentation across several points and water courses. The advance of the agricultural frontier in the region, particularly towards the plateau areas, takes place with the cultivation of soy, corn, and beef cattle.…”
Section: Study Areamentioning
confidence: 99%
“…Definidos como planes maestros que tienen como objetivo fundamentar y orientar la implementación de la PNRH y la gestión de los recursos hídricos en el territorio brasileño, los planes de recursos hídricos para las cuencas hidrográficas son planes a largo plazo, generalmente entre diez y veinte años, con revisiones periódicas, que deben ser compatibles con la implementación de los programas y proyectos planificados (ANA, 2013a). Estos son fruto del estudio, diálogo y consenso a respecto de la real situación de los recursos hídricos en escenarios distintos (Rabelo et al, 2021). Su contenido debe describir en detalle la situación de los recursos hídricos en las cuencas hidrográficas, los pronósticos de presiones futuras y posibles conflictos, los objetivos de racionalización del uso y mejora de la calidad de los recursos hídricos, las prioridades de otorgamiento, lineamientos y criterios de cobro por uso, entre otros (Brasil, 1997).…”
Section: Planes De Recursos Hídricos En Las Leyes De Aguas En Brasil Y Españaunclassified